2021
DOI: 10.13057/biodiv/d220827
|View full text |Cite
|
Sign up to set email alerts
|

A spatial model of forest and land fire vulnerability level in the Dairi District, North Sumatra, Indonesia

Abstract: Abstract. Thoha AS, Triani H. 2021. A spatial model of forest and land fire vulnerability level in the Dairi District, North Sumatra, Indonesia. Biodiversitas 22: 3319-3326. Fires often occur every dry season and have a significant impact on ecosystems and human activities. One of the important roles in reducing the risk of forest and land fires is the availability of updated vulnerability level maps in all vulnerable areas. The objective of this study was to determine the relationship between the driving fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The land that converted land cover change to non-forest experienced increased fire activity. Based on study [8,9] also confirmed that non-forest land namely shrubs, reeds and dryland farming, are the main source of land fires in North Sumaetra region. A study by [10] found that land cover change after forest and land fires, where forest and shrub cover turned into plantations.…”
Section: Land Cover Changes Of Sumatran Orangutan Habitat In Gnlp Of ...mentioning
confidence: 77%
“…The land that converted land cover change to non-forest experienced increased fire activity. Based on study [8,9] also confirmed that non-forest land namely shrubs, reeds and dryland farming, are the main source of land fires in North Sumaetra region. A study by [10] found that land cover change after forest and land fires, where forest and shrub cover turned into plantations.…”
Section: Land Cover Changes Of Sumatran Orangutan Habitat In Gnlp Of ...mentioning
confidence: 77%
“…The land cover in the Dieng Kulon village was classified using the Geographical Information System (GIS) (Thoha and Triani 2021). The method starts with retrieving the Dieng Kulon boundary and Landsat 8 Operational Land Imager (OLI) images of this village with a spatial resolution of 30 m per pixel.…”
Section: Land Cover Analysismentioning
confidence: 99%
“…The data shows that almost all areas included in the Miu sub-watershed are on steep to very steep slopes. This is one of the factors causing the rapid flow of water into rivers which causes high flood intensity [21,22]. The scoring slope map can be seen in Figure 1 (a).…”
Section: Flood Vulnerability Mappingmentioning
confidence: 99%